2015
DOI: 10.1093/jxb/erv346
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the repertoire of secretory peptides controlling root development with comparative genome analysis and functional assays

Abstract: HighlightComparative genome analysis combined with transcriptome mining identified secreted peptides possibly involved in root development. When applied on Arabidopsis roots, selected candidates affected growth or branching in specific ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 70 publications
3
87
1
Order By: Relevance
“…First, a homology search using representative proteins from established SSP families was performed. Second, HMMs of known or putative plant SSPs from the PlantSSP database (Ghorbani et al, 2015) were searched for matches. Third, to identify additional SSPs, short (less than 200 amino acids) and secreted (SignalP D-value .…”
Section: Identification Of M Truncatula Members Of Established Ssp Fmentioning
confidence: 99%
See 3 more Smart Citations
“…First, a homology search using representative proteins from established SSP families was performed. Second, HMMs of known or putative plant SSPs from the PlantSSP database (Ghorbani et al, 2015) were searched for matches. Third, to identify additional SSPs, short (less than 200 amino acids) and secreted (SignalP D-value .…”
Section: Identification Of M Truncatula Members Of Established Ssp Fmentioning
confidence: 99%
“…The pipeline employed the MAKER software program with expression evidence from 64 in-house RNA-seq libraries of diverse tissue types and developmental stages, the M. truncatula EST Gene Index 11, and protein sequences from L. japonicus, Glycine max, and the Swiss-Prot manually curated protein database. SPADA was used to identify SSP gene models using HMMs from the PlantSSP database (Ghorbani et al, 2015) and the in-built HMMs of Cys-rich families, which facilitated the identification of sORFs. Finally, the sORF Finder program (Hanada et al, 2010) was run specifically on the Mt4.0 genome to identify sORF gene models from intergenic regions.…”
Section: Identification Of M Truncatula Members Of Established Ssp Fmentioning
confidence: 99%
See 2 more Smart Citations
“…1,8,9 The CLE genes have been found in many plant species, whereas the roles of most identified CLE genes remained to be elucidated. 2,[10][11][12][13][14][15] As the 2 most known members of CLE peptide family, AtCLV3 and AtCLE40 are key regulators in coordinating stem cell homeostasis in the SAM (Shoot Apical Meristem) and RAM (Root Apical Meristem), respectively. 1 Other than their functions in stem cell fate, it has been also revealed that the CLE peptides are important players in modulating various plant growth and developmental processes such as nodulation, [16][17][18] protoxylem formation, 19 embryogenesis and endosperm development, 20 phloem formation, 21 pollen growth, 22 and lateral root expansion.…”
Section: Introductionmentioning
confidence: 99%